Two‐Stage Sulfide Mineral Assemblages in the Mineralized Ultramafic Rocks of the Laowangzhai Gold Deposit (Yunnan, SW China): Implications for Metallogenic Evolution. Issue 3 (3rd April 2019) - Zhang, Huichao; Chai, Peng; Zhang, Hongrui; Hou, Zengqian; Chen, Shouming; Sun, Yanbin; Peng, Qing
Abstract: The Laowangzhai gold deposit, located in the Ailaoshan gold belt (SW China), is hosted in various types of rocks, including in quartz porphyry, carbonaceous slate, meta‐sandstone, lamprophyre, and altered ultramafic rocks. In contrast to other wall rocks, the orebodies in altered ultramafic rocks are characterized by the occurrence of a large amount of Ni‐bearing minerals. The ore‐forming process of the orebodies hosted by altered ultramafic rocks can be divided into two stages: pyrite‐vaesite‐native gold and gersdorffite‐violarite stages. The contents of As and Sb increased during the evolution of ore‐forming fluid based on the mineral assemblages. Thermodynamic modeling of the Ni‐Cu‐As‐Fe‐S system using the SUPCRT92 software package with the updated database of slop16.dat indicates the f S2 in ore‐forming fluid decreases significantly from stage I to stage II. The decreases of f S2 due to crystallization of sulfides and f O2 due to fluid–rock reaction were responsible for ore formation in altered ultramafic rocks of the Laowangzhai gold deposit. Geological evidence, the in situ sulfur isotope values of pyrite, and the other published isotopic data suggest that the ore‐forming fluid for ultramafic rock ores was dominantly composed of evolved magmatic fluid with the important input of sediments. Abstract : The oreforming process of the orebodies hosted by altered ultramafic rocks can be divided into two stages: pyrite‐vaesite‐native gold and gersdorffite‐violarite stages. Thermodynamic modeling of the Ni‐Cu‐As‐Fe‐S system using the SUPCRT92 software package with the updated database of slop16.dat indicates the fS2 in ore‐forming fluid decreases significantly from stage I to stage II.